2019
DOI: 10.1007/s00784-019-02867-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circulating DNA in plasma of patients after allogeneic bone grafting

Abstract: Objectives Cell-free DNA (cfDNA) harboring mutations has been found in patients with diseases. Experimental studies have shown that cfDNA can be transmitted, leading to transformations in the host. In the present study, we evaluated whether bone allograft material contains cfDNA and whether this foreign cfDNA can be released into the patient's blood circulation. Materials and methods Plasma samples were collected preoperatively and postoperatively on the same day, at 5 weeks, and 4 months from 25 women who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Sample size per group did not need to be increased to control for attrition bias. The sample size was calculated using G power software and derived from our previous study [ 44 ]. Therefore, a sample size of 18 patients in each treatment group was considered to be sufficient to meet the primary objective of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size per group did not need to be increased to control for attrition bias. The sample size was calculated using G power software and derived from our previous study [ 44 ]. Therefore, a sample size of 18 patients in each treatment group was considered to be sufficient to meet the primary objective of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Reason for Exclusion Aghazadeh et al, 2012 [140] Application of granular autograft Arenaz-Búa et al, 2010 [141] Application of granular autograft Barboza et al, 2010 [142] Application of allogeneic bone granules Beitlitum et al, 2018 [143] Application of allogeneic bone granules Bianconi et al, 2017 [144] Alveolar ridge preservation Charde et al, 2020 [145] Block used for peri-implant bone regeneration Naishlos et al, 2021 [146] Blocks used for sinus floor augmentation Corinaldesi et al, 2009 [147] Application of autogenous bone granules El Chaar et al, 2019 [148] Application of allogeneic bone granules Ge et al, 2017 [149] Application of granular autograft Güven and Tekin, 2006 [150] Wrong indication (cyst filling) Huang et al, 2016 [151] Application of allogeneic bone granules Ilankovan et al, 1998 [152] No outcome of interest reported Jacotti et al, 2012 [153] Sample size too small Kang et al, 2015 [154] Particulated iliac bone applied with sinus lift Khoury and Hanser, 2015 [155] No outcome of interest reported Krasny et al, 2018 [156] Inclusion of patients with follow-up of less than 12 months Lekholm et al, 1999 [157] Application of different surgical approaches, missing patient information [160] Application of granular materials Merli et al, 2020 [161] Application of granular grafting materials Morad and Khojasteh, 2013 [162] Sample size too small Mordenfeld et al, 2017 [163] Application of granular autograft Özkan et al, 2007 [164] Sample size too small Pimentel et al, 2014 [165] Sample size too small Putters et al, 2018 [166] No outcome of interest reported Quereshy et al, 2010 [167] Sample size too small Sethi et al, 2020 [168] Inclusion of patients with follow-up < 12 months Simion et al, 2001 [169] Application of granular materials Simon et al, 2000 [170] Surgical technique (ARP) Soehardi et al, 2009 [171] No differentiation between onlay block and sinus floor elevation Solakoglu et al, 2019 …”
Section: Studymentioning
confidence: 99%
“… 44 Allogeneic bone transplantation is faced with the limitation of donor sources and immune rejection. 45 Autologous bone transplantation is faced with self-damage. 46 Therefore, the use of osteogenic drugs is ideal to induce bone tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%